Pengembangan Model Pembelajaran Matematika Berbasis Teknologi Digital untuk Meningkatkan Kemampuan Berpikir Kritis Siswa di Era Society 5.0 : The Development of a Digital Technology-Based Mathematics Learning Model to Enhance Students' Critical Thinking Skills in the Society 5.0 Era - Yusmaini, Yusmaini (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research aims to develop a digital technology-based mathematics learning model to enhance students' critical thinking skills in the Society 5.0 era. The study employed a Research and Development (R&D) method, encompassing the stages of needs analysis, model design, prototype development, expert validation, limited trials, and revision. The research subjects were 120 eighth-grade junior high school students from three different schools. The developed learning model integrates digital technologies such as GeoGebra, Kahoot, and online learning platforms with a problem-based learning approach. The expert validation results indicated that the learning model is highly valid, with an average score of 4.2 out of 5. The limited trials revealed a 68% increase in students' critical thinking skills, with a gain score of 0.72 (high category). Student and teacher responses to the learning model showed satisfaction levels of 85% and 92%, respectively. The learning model is proven effective in enhancing students' critical thinking skills through the integration of digital technology that aligns with the characteristics of digital natives in the Society 5.0 era.